Caracterización biológica de dos aislados de Leptospira spp. procedentes de pacientes colombianos con síndrome de Weil (2010)
ABSTRACT: The dynamics of experimental infection in a hamster model are described for two Leptospira spp. isolates, recovered from patients with Weil’s syndrome from towns in Antioquia. Experimental infection was performed by intraperitoneal inoculation of juvenile hamsters. The evaluation of markers of liver and kidney function as well as an acute phase reactant was performed at two time points post-infection. At 18 days post-inoculation the end point was set, blood was collected and an autopsy was performed, taking tissue from liver, kidney and lung for cultivation in EMJH and buffered formalin for histopathological studies. The results of tests for renal function, liver and C-reactive protein were variable, and even though they showed slight increases they were not correlated with the presence of clinical signs; however, at the histopathology level one might expect significant changes, since growth was obtained from the cultivation of kidney and liver in some animals. The results of the evaluation of virulence by determining the lethal dose 50 suggests that the two isolates were of low virulence or that virulence had been lost perhaps due to the successive passes in vitro before inoculation of the animals.